To solve the equation, we need to subtract the term 11/3 from both sides:
5/3x + 11/3 - 11/3 = -4/3 - 11/3
This simplifies to:
5/3x = -15/3
Next, to isolate x, we need to multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5) * (5/3x) = (3/5) * (-15/3)
The left side simplifies to:
(3/5) * (5/3x) = x
The right side simplifies to:
(3/5) * (-15/3) = -45/15 = -3
So the complete solution is:
x = -3
The equation 5/3x+11/3=−4/3 is solved as follows. Fill in the correct numbers to complete the solution. 5/3x+11/3=−4/3 5/3x= Subtract 11/3 from both sides. x= Multiply both sides by 3/5, the reciprocal of 5/3.
1 answer